SURGICAL TREATMENT OF AN UNUSUALLY LARGE MANDIBULAR RESIDUAL CYST: A CASE REPORT - Mateva, Aleksandra; Nikolovski, Bruno; Stamatoski, Aleksandar; Koneski, Filip; Ivanovski, Gjorgi; Dukovska, Daniela Bajdevska; Iliev, Aleksandar (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Residual cysts are common after the extraction of a third impacted molar. Many of them are usually asymptomatic and can be detected incidentally on routine radiography before symptoms appear. Lately, 3D CBCT is the most common diagnostic method for detecting them. We present a case of a residual cyst that exists 20 years after extraction of the right lower third molar. Cysts can vary in size, and over the years can grow and disrupt bone continuity. In this case, a 53-year-old patient has painless swelling that manifests extra-orally in the buccal and masseteric regions. It has been recurring in recent years but the condition was improving with the administration of antibiotic therapy. Surgical treatment is the method of choice. Diagnosis and management of the patient are discussed. Keywords: odontogenic cyst, residual cyst, operative extraction, third lower molar.